2012
DOI: 10.2306/scienceasia1513-1874.2012.38.356
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone improves spatial learning and memory in chronic cerebral hypoperfused rats

Abstract: Cerebral hypoperfusion is associated with cognitive decline in ageing, mild cognitive impairment, vascular type dementia, and Alzheimer's disease. The mechanisms leading to such neurological impairments are still uncertain. Although several mechanisms have been proposed as contributing factors leading to neuronal injury, glutamate excitotoxicity seems to be the relevant one. Recently, it was found that β-lactam antibiotics such as ceftriaxone show a neuroprotective effect by upregulation of glutamate transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Activated NF-kB binds to the GLT-1 promoter region and upregulates the transcription of this gene [45], thereby decreasing glutamate concentration in the synaptic cleft and alleviating the potentially neurotoxic effects of excess glutamate [46]. In some studies, it was also found that CEF treatment can attenuate neuronal injury and improve spatial learning and memory [47]. In some studies, CEF was also reported to mediate activation of glutathione through increased nuclear factor erythroid 2-related factor 2 (Nrf2) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Activated NF-kB binds to the GLT-1 promoter region and upregulates the transcription of this gene [45], thereby decreasing glutamate concentration in the synaptic cleft and alleviating the potentially neurotoxic effects of excess glutamate [46]. In some studies, it was also found that CEF treatment can attenuate neuronal injury and improve spatial learning and memory [47]. In some studies, CEF was also reported to mediate activation of glutathione through increased nuclear factor erythroid 2-related factor 2 (Nrf2) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone mediated increased expression of GLT1 is possibly NF- Κ B mediated GLT1 promoter activation [ 56 ]. Ceftriaxone was found to improve spatial learning and memory in chronically cerebral hypoperfused rats suggesting role in AD [ 57 ]. Moreover, ceftriaxone decreased tau pathology and showed improvement in cognitive functions [ 58 ].…”
Section: Reactive Astrocytes As a Potential Target For Alzheimer'smentioning
confidence: 99%
“…All rats were anesthetized with an intraperitoneal injection of ketamine (60 mg/kg) and xylazine (0.6 mg/kg) mixture [22]. After the rats were unconscious, the neck region was cleansed with 70% alcohol.…”
Section: Surgical Proceduresmentioning
confidence: 99%